2020
DOI: 10.21608/ijma.2020.46734.1193
|View full text |Cite
|
Sign up to set email alerts
|

Relation between iron status and hemoglobin A1c in children with type 1 Diabetes Mellitus

Abstract: Background: Hemoglobin A1c [HbA1c] is the best standard for measurements of glycemic control level in type 1 diabetes mellitus, especially in children. As iron deficiency anemia is a prevalent finding in children with diabetes, it may affect HbA1c levels in those children. Aim of the work:To determine the effects of iron deficiency anemia on hemoglobin A1c in type 1 diabetes mellitus Patients and methods: This was cross-sectional analytic study was done on 80 children with diabetes with type 1DM receiving insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…So far, only small studies with similar objectives have been reported in child and adolescent populations. Research by El-Nezely et al (12). in 80 children on insulin therapy in Egypt found a significant increase in the HbA1c levels in a group of patients with iron deficiency, even after HbA1c had been stratified for glycemic control.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…So far, only small studies with similar objectives have been reported in child and adolescent populations. Research by El-Nezely et al (12). in 80 children on insulin therapy in Egypt found a significant increase in the HbA1c levels in a group of patients with iron deficiency, even after HbA1c had been stratified for glycemic control.…”
Section: Discussionmentioning
confidence: 98%
“…The effect of iron deficiency on the HbA1c levels was first investigated by Brooks et al (9) and several studies have reported similar results (10)(11)(12)(13)(14). Therefore, the potential effect of iron deficiency on the HbA1c levels should be observed by clinicians; additionally, the status of iron levels in children with T1DM should be adequately assessed before interpreting the HbA1c results (15).…”
Section: Introductionmentioning
confidence: 86%